Malignant Hyperthermia during Thoracoscopic Pulmorrhaphy in a 70-Year-Old Man - Michihiro Sakai; Noriko Murakami; Yuji Kitamura; Shin Sato; Hiroshi Iwama; Akira Nomura (Case Reports in Anesthesiology)
Malignant hyperthermia (MH) is a rare but potentially fatal complication that may develop under general anesthesia (GA) and is rarely reported in elderly patients. We encountered a case of mild-onset MH in a 70-year-old patient who was receiving an elective thoracoscopic pulmorrhaphy and had a history of several GA procedures. Anesthesia was induced with propofol, fentanyl, and rocuronium and maintained with sevoflurane and remifentanil. His body temperature (BT) was 37.9°C after induction. During the procedure, the end-tidal CO2 (ETCO2) increased steadily to 47–50 mmHg, presumably in response to the single lung ventilation. At the end, BT was 38.1°C and ETCO2 was 47 mmHg under spontaneous breathing. After extubation, the patient wheezed on inspiration and expiration, and his trachea was reintubated. Sixty minutes after surgery, BT increased to 40.5°C and the arterial blood gas analysis showed severe metabolic acidosis. Based on these findings, MH was suspected and a bolus dose of dantrolene was administered. He responded to the dantrolene, and no complications or recurrence of MH was observed postoperatively. In this patient, the initial signs of MH were so subtle that making the diagnosis of MH was difficult. A high degree of suspicion is necessary to prevent a fulminant MH crisis.